Aktivitas Fisik Rutin untuk Mencegah Penyakit Degeneratif - Kesetyaningsih, Tri Wulandari; Astuti, Yoni; Noor, Zulkhah (Universitas Muhammadiyah Yogyakarta, 2020)
Degenerative or metabolic disease is a disease caused by excessive activities that give people no time to maintain their body health. This continuous condition can increase the death risk. This phenomenon is widely found with the existence of obesity in many places including in Gamping hamlet, Ambarketawang village, Gamping district, Sleman regency. Recently, the trend of this disease has gone up. Therefore, creating the society’s awareness about this issue is necessary to do through an empowerment program. This program is expected to decrease the death risk caused by metabolic or degenerative disease mainly for housewives who have never-ending activities. The society empowerment program is implemented through an organization for women namely Family Welfare Program. This program implementation is done in some stages namely:1) early physical quality examination (body mass index, blood pressure, cholesterol levels, blood sugar and uric acid); 2) a group creation that concerns about healthy life; 3) socialization on healthy life pattern; 4) psychomotor routine gymnastics twice a week for 10 weeks; and 5) final physical quality examination. It is recorded from this empowerment program that 38.29 % suffers from obesity, 6.38 % suffers from diabetes mellitus (DM), 36.17 % suffers from high uric acid and 10.64 % suffers from hypercholesterolemia. After regular gymnastics twice a week in 10 weeks, it is recorded that the obesity decreases to 34.04 % and the DM decreases to 4.26%, while hypercholesterolemia increases to 17.02%. The uric acid, on the other hand, remains stable. To maintain their further health, continuous routine gymnastics, periodic medical check-up (at least once a year), especially for people aged 40 years. Another success of this program is the creation of Healthy Life Caring Community.